An Iron Metabolism-Related Gene Signature for the Prognosis of Colon Cancer - Yuan, Jing; Liu, Tao; Zhang, Yuhong (Frontiers in Cell and Developmental Biology, 2022)
As an essential microelement, the iron ion is involved in cell proliferation, metabolism, and differentiation. Iron metabolism plays a crucial role in the occurrence and development of colon adenocarcinoma (COAD). In this study, univariate and multivariate Cox regression, and least absolute shrinkage and selection operator analyses were conducted to construct the gene signature, based on a dataset from The Cancer Genome Atlas. We identified the prognostic value of two iron metabolism-related genes [SLC39A8 (encoding solute carrier family 39 member 8) and SLC48A1 (encoding solute carrier family 48 member 1)] in COAD. A nomogram model was established to predict the overall survival of patients with COAD. Functional analysis showed that the tumor microenvironment and immune cell infiltrate were different between the low risk and high risk subgroups. This study verified that the iron metabolism-related gene signature (SLC39A8 and SLC48A1) could be used as a prognostic biomarker for patients with COAD.